2008
DOI: 10.1093/aje/kwn017
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Outcomes of Serious Attempted Suicide: A Nationwide Study in Finland, 1996-2003

Abstract: Suicide is among the 10 leading causes of death. Attempted suicide is 10-40 times more frequent than completed suicide and is the strongest single predictor of subsequent suicide. The current study population included all persons in Finland who were hospitalized with a diagnosis of attempted suicide between 1996 and 2003 (N = 18,199). Information on background variables and mortality was obtained by register linkage. The risk of repeated attempted suicide was 30% and the risk of suicide was 10%. The risks of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
114
3
36

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(172 citation statements)
references
References 39 publications
19
114
3
36
Order By: Relevance
“…Haukka et al [24] reported the risk of suicide in Finland to be as high as 10%, with a risk of repeated attempts of 30%. The reported suicide rate in neighboring countries that are similar to the UAE is very low.…”
Section: Discussionmentioning
confidence: 99%
“…Haukka et al [24] reported the risk of suicide in Finland to be as high as 10%, with a risk of repeated attempts of 30%. The reported suicide rate in neighboring countries that are similar to the UAE is very low.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Sjálfsvígstilraunir eru taldar 3-40 sinnum fleiri en sjálfsvíg 1,3,7 en tilraun til sjálfsvígs er talin vera sá áhaettuþáttur sem hefur hvað sterkust tengsl við síðara sjálfsvíg. 1,8 Karlar eru taldir í meiri sjálfsvígsáhaettu eftir sjálfs-vígstilraun en konur og einnig miðaldra og eldra fólk miðað við yngri einstaklinga. 9,10 Árlega koma um 500 manns á bráðadeildir Landspítala vegna sjálfsvígstilrauna eða sjálf-skaða.…”
Section: Inngangurunclassified
“…17 Þetta er í samraemi við nýlega rannsókn á alvarlegum sjálfsvígum í Finnlandi þar sem litið var á alla þá sem þurftu á sjúkrahúsvist að halda eftir sjálfvígstilraun. 1 Mjög hátt hlutfall hópsins (61%) hafði áður gert sjálfsvígstilraun og var það nánast jafnt meðal karla og kvenna sem bendir til þess að þessi hópur sé frábrugðinn hinum almenna hópi sem kemur á bráðamóttöku vegna sjálfsskaða.…”
Section: Sjúklingahópurinnunclassified
See 1 more Smart Citation
“…Risk factors like past suicide attempts, family history, access to guns and other weapons, life stressors, adverse personal experiences (rape, sexual abuse), and terminal illness should be carefully evaluated and addressed appropriately through counseling or hospitalization, if necessary [5]. The core care team of physicians, therapists and healthcare personnel are responsible for identifying potential patients for suicide risk and encouraging them to discuss their problems with their family or doctors, essentially circumventing suicide via more appropriate solutions.…”
mentioning
confidence: 99%